The Application Of Attractiveness, Competency, Responsibility, And Empathy In Improving The Accounting Department Students Existence Effect - Permatasari, Devi (Economics and Business Solutions Journal, 2017)
This research aims at investigating the application of the factors in improving the existence effect of students of Accounting Departmentat Economics Faculty, Unissula. The population in this research is all undergraduate (S1) and associate (D3) degree students of Accounting Department at Economics Faculty, Unissula. Meanwhile, the sample used in this research amounts to 169 respondents who are undergraduate (S1) and associate (D3) degree students of Accounting Department at Economics Faculty, Unissula taking such courses as Management Information System, IT Literacy, and Financial Statements Analysis. The hypotheses are tested using analysis of multiple linear regression from SPSS program. Based on the results of hypothesis testing, it can then be concluded that the existence effect of students of Accounting Department, at both undergraduate (S1) and associate (D3) degrees are significantly influenced by such factors as attractiveness, competency, and empathy.